Integrating Sustainability and Maqashid Shariah in Islamic Banking: A Systematic Literature Review - Nurma Yulita (Salam (Islamic Economics Journal), 2025)
Sustainability issues recently become more prominent in the Islamic banking sector, accompanied by efforts to incorporate the values of Maqasid Sharia. This study aims to analyze and visualize scholarly works regarding the amalgamation of ESG and Maqasid Sharia in Islamic Banking from 2021 to 2025. This paper employs Systematic Literature Review (SLR) methodology, adhering to PRISM guidelines, and utilizing various prominent scientific databases to conduct targeted queries and thematic analyses of the chosen articles. The study concludes that there is theoretical and empirical alignment between the maqasid sharia and ESG, particularly regarding the protective stewardship of the environment, public and social equity, and ethical governance. Sharia-based sustainable financing is empirically supported by various financial instruments like green sukuk and waqf sukuk. The merging of these fields, however, still poses social protection and financial education complexities.Thus, for the integration of the ESG (Environmental, Social, and Governance) and the Maqasid Sharia (Objectives of Islamic Law) to be implemented in all aspects of Islamic banking, infrastructure, innovations in Islamic banking products, regulatory, and support investments in human resources and technology are required. Keywords : Sustainability, Maqashid Shariah, and Islamic Banking